1956
DOI: 10.1085/jgp.39.5.801
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation of Myxomyosin, an Atp-Sensitive Protein From the Plasmodium of a Myxomycete

Abstract: 1. A procedure has been developed for the preparation of an active concentrate from the myxomycete, Physarum polycephalum. This concentrate responds with a lowered viscosity to the addition of small amounts of ATP. The preparation recovers in viscosity, and the process may be repeated. 2. In the most active concentrates, 75 per cent of the non-dialyzable material moves as a single boundary both in the descending limb in electrophoresis and in the ultracentrifuge. It contains about 10 per cent ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1962
1962
1986
1986

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…He believes that this reconciles morphological findings with the physiological studies of Loewy (30). Kamiya (24,25), and Ts'o et al (68) and that the fibrils contract to produce a local pressure which is active streaming, but these were also found in some plasmodia in which streaming could not be seen.…”
Section: + + +supporting
confidence: 58%
See 2 more Smart Citations
“…He believes that this reconciles morphological findings with the physiological studies of Loewy (30). Kamiya (24,25), and Ts'o et al (68) and that the fibrils contract to produce a local pressure which is active streaming, but these were also found in some plasmodia in which streaming could not be seen.…”
Section: + + +supporting
confidence: 58%
“…In a later study, Dugas and Bath (10) mention the question of the presence of fibrils, but in discussing their electron microscopic observations on sec- tions of the plasmodium of P. polycephalum they do not refer to fibrils. Others who have studied protein extracts of the plasmodium of this same species have reported network arrangements or rigid rods (68), but Stewart and Stewart (63) could find no such structures in sections of plasmodia fixed from the living state. They suggest that, since fibril formation often occurs as a post mortem change, these fibrils might not be present in vivo.…”
Section: Contractile Component and Fibrils In Myxomycete Plasmodiamentioning
confidence: 96%
See 1 more Smart Citation
“…These fibrils have been shown histochemically to contain ATPase, the enzyme which biochemical studies of the actomyosin and myxomyosin (or plasmodial myosin B) systems would lead us to expect to find in the fibrils. Furthermore, Wohlfarth-Bottermann's electron microscopic studies have revealed filamentous structures within the microscopically observable fibrils which are apparently made up of elongated molecules similar in size to those in myxomyosin studied by Ts'o et al (25)(26)(27)(28). Thus, there are good grounds for believing that the birefringent fibrils described here are composed of "contractile pro-H1ROMICHI NAKAJI~ AND ROBERT D. ALLEN Birefringence in Plasmodia tein" similar to that of the fractions prepared from plasmodia by Ts'o et al and by Nakajima (15)(16)(17).…”
Section: Discussionmentioning
confidence: 91%
“…There is also evidence, in slime mould at least, that the fibrils involved in streaming have aftinities with the actomyosin of muscle. Thus protein fractions have been isolated from slime moulds by various authors, and shown to have chemical and physical properties similar to muscle actin or muscle myosin (Loewy, 1952;Ts'o, Eggmann & Vinograd, 1956, 1957aNakajima, 1960;Hatano & Oosawa, 1966a, b: Hatano & Tazawa, 1968. Wohlfarth-Bottermann (1963 has shown that the slime mould fibrils have ATP-ase activity.…”
Section: B Streaming In the Slime Mould Physarum Polycephalummentioning
confidence: 99%